PROVIDING A LEGAL DEFINITION FOR CYBERBULLYING IN SOUTH AFRICA - Sershiv Reddy (Obiter, 2023)
Traditional bullying is not a new phenomenon, and this behaviour has plagued many countries. It has received a wide interpretation by many academics seeking to define this concept. Bullying itself may take various forms and it has developed and adapted to changing times throughout history. One such adaptation arose owing to the expansion of the Internet – in the form of online bullying or cyberbullying. Although bullying has been given various definitions, cyberbullying in South Africa has not been given a legal definition, and perpetrators are therefore not disciplined in the appropriate manner. Introducing a legal definition would assist law enforcement to regulate cyberbullying and protect victims from harm. Advances in technology have created many opportunities for people to communicate across the world. At the same time, they have also created unintended consequences, such as allowing online users to harm each other. Although bullying has existed for a long time, the threat of cyberbullying online is arguably worse than its traditional counterpart. Scholars have attempted to provide definitions of cyberbullying. However, there is confusion and there are contradictory views regarding the characteristics of this conduct. Recommendations are made on what the requirements should be for a legal definition of cyberbullying. A comparative analysis of the United States and Canada is relied upon to establish clarity on this conduct.